Computer simulation for gold nanoparticles - He, Peiming (2015)
Gold (Au) nanoparticles and nanoclusters have been popular over the last 30 years due to their intriguing morphology and unique catalytic properties, especially as a catalyst in oxidation processes of carbon-monoxide (CO). The thermodynamic studies of Au nanoparticles have unraveled a great number of significant morphological properties of Au nanoparticles and nanoclusters. Numerous Wulff construction methods have been utilized in the understanding of these morphological properties discovered. Moreover, certain magic numbers of construction and transition threshold sizes of structures have been identified. In this report, we take a perspective of thermodynamics to uncover the mysteries behind these transition threshold values. Though the traditional Wulff construction is a powerful tool, it can no longer satisfy current studies to a bimetallic nanoparticle system. By utilizing the modified Wulff construction to corporate the kinetic factors, we then discuss our findings in the area of alloyed nanoparticles of Au as well as nanoparticle growth.